PUSAT OLEH – OLEH KALIMANTAN SELATAN DI BANJARMASIN - Asdani, Agusti Dwi; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The design of South Kalimantan Souvenir Center is motivated by the number of tourists visiting South Kalimantan, especially Banjarmasin. One of the influential needs of the increase in tourists is the need for local specialties. Souvenir shops in Banjarmasin currently are less representative, so the existence of a souvenir center that sells a variety of South Kalimantan specialty products in one place that has local characteristics so that tourists not only shop but also get a tour experience. The problem solving method applied is the Metaphor Architecture method which refers to the building design stage as a certain character from a formation or object that is unique to Banjarmasin. The design concept applies the concept of one stop shopping where this souvenir center is able to accommodate a variety of typical products of South Kalimantan in one place. The result of the design is in the form of a building design that can become one of the icons of the city of Banjarmasin that accommodates souvenir shopping facilities in one place.